A method for preparing an aluminum electrolytic capacitor

By using double-layer electrolytic paper prepared with bamboo pulp fiber and wood pulp fiber, combined with the adsorption of conductive graphite and the impregnation treatment of electrolyte, the problems of poor impact resistance and high equivalent series resistance of the electrolytic paper of aluminum electrolytic capacitor are solved, and higher reliability and longer service life are achieved.

CN119208017BActive Publication Date: 2025-04-15SHANGHAI YONGMING ELECTRONIC CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411564976.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-04-15
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The electrolytic papers of existing aluminum electrolytic capacitors have problems such as poor impact resistance, high equivalent series resistance and low reliability.

Method used

Bamboo pulp fiber and wood pulp fiber are used to prepare double-layer electrolytic paper. The microporous layer is arranged close to the anode foil to adsorb conductive graphite, and the performance of electrolytic paper is improved through impregnation treatment and chemical repair treatment.

Benefits of technology

It significantly improves the high-voltage AC impact resistance of aluminum electrolytic capacitors, reduces the equivalent series resistance, improves reliability, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a method for preparing an aluminum electrolytic capacitor, and relates to the technical field of capacitors. The method comprises at least the following steps: winding an anode foil, a double-layer electrolytic paper and a cathode foil into a core package; performing an impregnation treatment on the core package; drying the impregnated core package into a shell to form an aluminum electrolytic capacitor; wherein the double-layer electrolytic paper comprises a microporous layer and a substrate layer, and the microporous layer is arranged close to the anode foil, conductive graphite is adsorbed on the microporous layer, the raw material of the microporous layer is bamboo pulp fiber, and the raw material of the substrate layer is bamboo pulp fiber and wood pulp fiber. The electrolytic paper of the aluminum electrolytic capacitor prepared in the present application comprises a microporous layer and a substrate layer, and conductive graphite is attached to the microporous layer, which effectively improves the high-voltage AC shock resistance and cycle performance of the aluminum electrolytic capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitors, and in particular to a method for preparing an aluminum electrolytic capacitor. Background Art

[0002] With the rapid development of the global electronics industry and information industry, aluminum electrolytic capacitors have been brought a new huge market, but also posed new challenges. The requirements for miniaturization, stability, high performance and low cost of aluminum electrolytic capacitors are becoming more and more urgent. In particular, high capacity and miniaturization have greatly affected the miniaturization and integration of electronic circuits. Therefore, the development of aluminum electrolytic capacitors with small size, large electrostatic capacity, long service life and low price has become a hot topic in current research, and it also breeds huge business opportunities and a broad market.

[0003] Electrolytic paper is the core material for the production of aluminum electrolytic capacitors. It plays the role of isolating the anode foil and the cathode foil in the capacitor to prevent short circuit between the anode and the cathode. At the same time, it can absorb the working electrolyte and play the role of the cathode carrier. At the same time, it has excellent high temperature resistance, corrosion resistance and mechanical strength. The performance and quality of electrolytic paper have a great impact on the performance of aluminum electrolytic capacitors. At present, aluminum electrolytic capacitors are developing in the direction of low loss, low impedance and miniaturization. Electrolytic paper plays a key role in improving the working voltage of aluminum electrolytic capacitors and extending the life of aluminum electrolytic capacitors. Therefore, promoting the low loss and low impedance of electrolytic paper and improving electrical strength have become important directions for the research and development of electrolytic paper. At present, although aluminum electrolytic capacitor electrolytic paper has been in development, the types of materials used are relatively small. Therefore, it is urgent to find new materials or methods for preparing aluminum electrolytic capacitor electrolytic paper and improving the performance of aluminum electrolytic capacitors. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an aluminum electrolytic capacitor to solve the following technical problems:

[0005] The existing electrolytic paper of aluminum electrolytic capacitors has the problems of poor impact resistance, high equivalent series resistance and low reliability.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing an aluminum electrolytic capacitor comprises at least the following steps:

[0008] Winding the anode foil, the double-layer electrolytic paper and the cathode foil into a core package;

[0009] Performing an impregnation treatment on the core package;

[0010] Drying the impregnated core package into a shell to form an aluminum electrolytic capacitor;

[0011] The double-layer electrolytic paper comprises a microporous layer and a substrate layer, and the microporous layer is arranged close to the anode foil, conductive graphite is adsorbed on the microporous layer, the raw material of the microporous layer is bamboo pulp fiber, and the raw material of the substrate layer is bamboo pulp fiber and wood pulp fiber.

[0012] As a further solution of the present invention: the thickness of the microporous layer is 30-50 μm, and the density is 0.55-0.70 g / cm 3 .

[0013] As a further solution of the present invention: the thickness of the substrate layer is 40-60 μm, and the density is 0.65-0.80 g / cm 3 .

[0014] As a further solution of the present invention: the preparation method of the double-layer electrolytic paper comprises the following steps:

[0015] After bamboo pulp and wood pulp are fully dispersed and mixed, they are transferred to a pulping machine for pulping, and then a papermaking machine is used to prepare a substrate layer;

[0016] After bamboo pulp is fully deflated, it is transferred to a pulping machine for pulping, and then a microporous layer is prepared using a papermaking machine;

[0017] Dispersing conductive graphite in a dispersant and spraying or soaking the microporous layer;

[0018] The substrate layer and the microporous layer adsorbing the conductive graphite are pressed and compounded, and then dried to obtain a double-layer electrolytic paper.

[0019] As a further solution of the present invention: the beating degree of the microporous layer is 90-95°SR, and the beating degree of the substrate layer is 85-90°SR.

[0020] As a further solution of the present invention: the weight concentration of the conductive graphite is 0.01-0.1 g / ml, and the dispersant is a dispersed aqueous solution of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate).

[0021] As a further embodiment of the present invention: the impregnation treatment comprises at least the following steps:

[0022] Impregnating the core package with the dispersion liquid to obtain a core package impregnated with the dispersion liquid;

[0023] impregnating the core package impregnated with the dispersion liquid with a forming liquid to obtain a formed core package;

[0024] The formed core package is impregnated with electrolyte to obtain a core package impregnated with electrolyte.

[0025] As a further embodiment of the present invention: the electrolyte includes at least one of boric acid, phosphoric acid and adipic acid, the dispersion liquid is a dispersed aqueous solution of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate), and the formation liquid is an aqueous solution of adipic acid amine.

[0026] Beneficial effects of the present invention:

[0027] The present application uses bamboo pulp fiber and wood pulp fiber to prepare a double-layer electrolytic paper structure, and conductive graphite is adsorbed on the microporous layer close to the anode foil. The obtained aluminum electrolytic capacitor has the advantages of high resistance to high-voltage AC shock, low equivalent series resistance and high reliability, which can significantly improve the electrical performance of the aluminum electrolytic capacitor and extend its service life. It can be widely used in home appliances, computers, servers, communication equipment, mobile phones, fast chargers, optoelectronic products, new energy, high-speed railways, aerospace, automotive industry, military industry and other fields.

[0028] The present application forms a microporous layer with bamboo pulp fiber and forms a substrate layer with bamboo pulp fiber and wood pulp fiber. The wood pulp fiber has the advantages of high density, voltage resistance, and resistance to aluminum foil burrs. The bamboo pulp fiber has the advantages of high water absorption, excellent electrical properties, excellent temperature characteristics, a wide operating temperature range and moderate price. In addition, during the preparation process, as the number of pulping revolutions increases, the beating degree of the fiber increases, and the corresponding tightness also gradually increases. A tightness difference is set between the microporous layer and the substrate layer. The greater the difference in tightness between the two layers, the higher the electrical strength of the diaphragm, the higher the liquid absorption height, and the lower the ESR value per unit thickness. The two are used in combination to ensure that the electrolyte on the surface of the cathode aluminum foil and the anode aluminum foil is sufficient to meet the smaller ESR requirement, so that the aluminum electrolytic capacitor has a strong ability to withstand high-voltage AC shocks, reduces production costs, and solves the problem of wood shortage to a certain extent.

[0029] In the present application, the substrate layer is formed by mixing bamboo pulp fiber and wood pulp fiber. During the preparation process, as the beating degree increases, the fiber length and fiber width in the pulp are continuously reduced, and the fine fiber content is continuously increased. The fine fiber content and curl index in the bamboo pulp are greater than those in the wood pulp pulp. The bamboo pulp fiber is dispersed in the electrolytic paper to form a rich, fine and uniform void structure. The electrolytic paper with this structure can absorb a sufficient amount of electrolyte in the capacitor, and the capacitor made has low impedance and low loss. The presence of fine fibers is similar to adding reinforcing materials to the electrolytic paper, which will not only increase the uniformity of the electrolytic paper and make the surface of the electrolytic paper more uniform when the external field is applied, but also fill a large number of pores between the electrolytic paper and reduce the pore size, thereby reducing the migration speed of the carriers inside the electrolytic paper in the electric field, increasing the injection amount of charge, making it more difficult to accumulate charge in the internal space of the electrolytic paper, reducing the damage of the electrons inside the electrolytic paper to the cellulose chain, increasing the breakdown strength of the electrolytic paper, and improving the ability of the obtained aluminum electrolytic capacitor to withstand high-voltage alternating current shock.

[0030] The present application also utilizes a dispersant containing conductive graphite to spray or soak the microporous layer first. The wood pulp fiber has good water absorption, and the formed pore structure is more abundant and uniform, so that the microporous layer can fully absorb the conductive graphite particles. After the poly(3,4-ethylenedioxythiophene) film is formed in the core package, the poly(3,4-ethylenedioxythiophene) is coated or covered with the conductive graphite powder. During the charge and discharge cycle, the conductive graphite powder can support the expansion and contraction of the poly(3,4-ethylenedioxythiophene) film, so that the poly(3,4-ethylenedioxythiophene) is not easy to separate from the surface of the anode foil. The supporting effect of the conductive graphite powder on the poly(3,4-ethylenedioxythiophene) is that the more uniformly the conductive graphite is dispersed in the core package, the better the effect. The poly(3,4-ethylenedioxythiophene): poly(styrene sulfonate) dispersion is used to make the poly(3,4-ethylenedioxythiophene) dispersed evenly. The conductive graphite powder not only supports poly(3,4-ethylenedioxythiophene), but also does not affect the structure and conductivity of poly(3,4-ethylenedioxythiophene). Moreover, the addition of the conductive graphite powder can reduce the internal resistance of the aluminum electrolytic capacitor and improve the cycle performance of the aluminum electrolytic capacitor. DETAILED DESCRIPTION

[0031] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] The preparation method of double-layer electrolytic paper comprises the following steps:

[0034] 25 g of wood pulp (absolute dry weight) fiber and 15 g of bamboo pulp (absolute dry weight) fiber were weighed, soaked in pure water for 24 h, and fully deflated by a fiber defiberizer. The pulp was prepared to a concentration of 10% and then transferred to a pulper for refining. The refining pressure of the pulper was set to 3.33 N / mm, and the beating degree was measured to be 85°SR. The ground pulp was collected, and after balancing the moisture content, it was deflated by a fiber defiberizer at 8000 r. A Kaiser automatic paper machine was used to prepare several sheets with a basis weight of 10 g / m 2 The substrate layer of the electrolytic paper is placed in a constant temperature and humidity chamber for 24 hours for standby use;

[0035] 30 g of bamboo pulp (absolute dry weight) fiber was weighed, added with pure water and soaked for 24 h, and after being fully deflated by a fiber deflagrator, the pulp was prepared to a concentration of 10% and transferred to a pulping machine for refining. The refining pressure of the pulping machine was set to 3.33 N / mm, and the beating degree was measured to be 90°SR. The ground pulp was collected, and after balancing the moisture content, it was deflated by a fiber decomposer at 8000r. A Kaiser automatic papermaking machine was used to prepare several sheets with a basis weight of 10 g / m 2 The microporous layer of the electrolytic paper of the single aluminum electrolytic capacitor is placed at 50°C and dried for 1 hour for use;

[0036] Conductive graphite powder is dispersed in a dispersed aqueous solution of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate), and ultrasonically vibrated for more than 5 hours, the weight concentration of conductive graphite in the dispersant is 0.05 g / ml, and the microporous layer is immersed for 1 hour, and then placed in a constant temperature and humidity chamber for 24 hours for use;

[0037] The microporous layer for adsorbing conductive graphite and the substrate layer are stacked, pressed and compounded by a flat press, and then dried by a rotary dryer to obtain a double-layer electrolytic paper.

[0038] The preparation method of aluminum electrolytic capacitor comprises the following steps:

[0039] Cutting the anode foil, the double-layer electrolytic paper and the cathode foil, and winding the anode foil, the cathode foil and the double-layer electrolytic paper into a core package by a core package winding machine, wherein the electrolytic paper is between the anode aluminum foil and the cathode aluminum foil, the microporous layer is arranged close to the anode foil, and the length of the electrolytic paper is longer than the length of the overlapping part of the anode and cathode aluminum foils, to obtain a core package;

[0040] The core package is placed in a sealed container and impregnated with a dispersion liquid under pressure, wherein the dispersion liquid is a dispersed aqueous solution of a conductive polymer poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate), the pressure of the pressurized impregnation is 8KG, the time of the pressurized impregnation is 10 minutes, and then the core package is placed at a temperature of 180° C. and dried for 90 minutes to obtain a core package impregnated with the dispersion liquid;

[0041] The core package impregnated with the dispersion liquid is immersed in a 5% mass concentration of adipic acid amine forming liquid, and voltage is applied to the positive and negative electrodes of the core package at the same time to perform a forming repair treatment for 20 minutes, wherein the voltage used is 12-16V and the current density is 0.01-0.03mA / pcs. After the core package is subjected to the forming repair treatment, the core package is placed at a temperature of 125°C and dried for 40 minutes to obtain a formed core package;

[0042] The core package after the chemical formation is immersed in an electrolyte containing triethylamine, phthalic acid and adipic acid, and voltage is applied to the positive and negative electrodes of the core package at the same time, and a vacuum pressure impregnation treatment is performed for 15 minutes, and then the core package is placed at a temperature of 125° C. and dried for 50 minutes to obtain a core package impregnated with the electrolyte;

[0043] The core package impregnated with electrolyte is assembled with an aluminum shell and a leather plug to obtain a semi-finished capacitor, and the semi-finished capacitor is charged and aged. Voltages are applied at 0.5 times, 1 times and 1.2 times the rated voltage respectively for segmented aging treatment. The aging temperature is 125° C. and the aging time is 120 minutes to obtain an aluminum electrolytic capacitor.

[0044] Example 2

[0045] In the preparation step of the double-layer electrolytic paper, 20 g of wood pulp and 20 g of bamboo pulp (absolute dry weight) fibers are weighed to prepare a substrate layer;

[0046] The remaining components and preparation method are exactly the same as those in Example 1.

[0047] Example 3

[0048] In the preparation step of the double-layer electrolytic paper, 30 g of wood pulp and 10 g of bamboo pulp (absolute dry weight) fibers were weighed to prepare a substrate layer;

[0049] The remaining components and preparation method are exactly the same as those in Example 1.

[0050] Example 4

[0051] In the preparation step of the double-layer electrolytic paper, the beating degree of the slurry for preparing the substrate layer is 90°SR, and the beating degree of the slurry for preparing the microporous layer is 95°SR;

[0052] The remaining components and preparation method are exactly the same as those in Example 1.

[0053] Example 5

[0054] In the preparation step of the double-layer electrolytic paper, the beating degree of the slurry for preparing the substrate layer is 85°SR, and the beating degree of the slurry for preparing the microporous layer is 95°SR;

[0055] The remaining components and preparation method are exactly the same as those in Example 1.

[0056] Comparative Example 1

[0057] The preparation method of electrolytic paper comprises the following steps:

[0058] 70g of wood pulp (absolute dry weight) fiber was weighed, added with pure water and soaked for 24h, and after being fully deflated by a fiber deflagrator, the pulp was prepared to a concentration of 10% and then transferred to a pulping machine for pulping. The refining pressure of the pulping machine was set to 3.33N / mm, and the beating degree was measured to be 85°SR. The ground pulp was collected, and after balancing the moisture content, it was deflagrated with a fiber decomposer for 8000r, and a Kaiser automatic papermaking machine was used to prepare several sheets with a basis weight of 10 g / m 2 The substrate layer of the electrolytic paper is squeezed and compounded by a flat press and then dried by a rotary dryer to obtain the electrolytic paper.

[0059] The preparation steps of the aluminum electrolytic capacitor are exactly the same as those in Example 1.

[0060] Comparative Example 2

[0061] The preparation method of electrolytic paper comprises the following steps:

[0062] 70g of bamboo pulp (absolute dry weight) fiber was weighed, added with pure water and soaked for 24 h, and after being fully deflated by a fiber deflagrator, the pulp was prepared to a concentration of 10% and transferred to a pulping machine for refining. The refining pressure of the pulping machine was set to 3.33N / mm, and the beating degree was measured to be 85°SR. The ground pulp was collected, and after balancing the moisture content, it was deflated by a fiber decomposer at 8000r. A Kaiser automatic papermaking machine was used to prepare several sheets with a quantitative of 10 g / m 2 The substrate layer of the electrolytic paper is squeezed and compounded by a flat press and then dried by a rotary dryer to obtain the electrolytic paper.

[0063] The preparation steps of the aluminum electrolytic capacitor are exactly the same as those in Example 1.

[0064] Comparative Example 3

[0065] In the preparation steps of the double-layer electrolytic paper, the slurry for preparing the substrate layer is 40 g of wood pulp (absolute dry weight) fiber;

[0066] The remaining components and preparation method are exactly the same as those in Example 1.

[0067] Comparative Example 4

[0068] In the preparation steps of the double-layer electrolytic paper, the step of adsorbing conductive graphite powder is omitted;

[0069] The remaining components and preparation method are exactly the same as those in Example 1.

[0070] Performance Testing

[0071] (1) Double-layer electrolytic paper performance test

[0072] The liquid absorption height test was carried out according to the national standard GB / T461.1-2002, the electrical breakdown strength test was carried out according to the national standard GB / T20628.2-2006, the tensile strength test was carried out according to GB / T12914-2008, and the breakdown voltage test was carried out according to the national standard GB / T12656-1990. The test results are shown in Table 1;

[0073] Table 1: Statistical table of electrolytic paper performance test data for Examples 1-5 and Comparative Examples 1-4

[0074]

[0075] It can be seen from Table 1 that the double-layer electrolytic paper prepared by the present application with adsorbed conductive graphite has excellent water absorption, tensile strength and electrical breakdown strength, and the breakdown voltage is above 440V. In Comparative Examples 1 and 2, single wood pulp or bamboo pulp is used to prepare electrolytic paper, and the liquid absorption height of the obtained electrolytic paper is better, but the electrical breakdown strength, tensile strength and breakdown voltage are poor; in Comparative Example 3, only wood pulp is used to prepare the substrate layer, and the liquid absorption height and tensile strength of the obtained electrolytic paper are poor; in Comparative Example 4, the conductive graphite powder is not adsorbed on the microporous layer, and the electrical breakdown strength and breakdown voltage of the obtained electrolytic paper are poor.

[0076] Aluminum electrolytic capacitor performance test

[0077] The capacitance (CAP) was measured at a frequency of 120 Hz, and the internal resistance and the capacitance after 5000 surge tests were measured at a rated voltage of 6.3 V. The test results are shown in Table 2.

[0078] Table 2: Statistical table of performance test data of aluminum electrolytic capacitors of Examples 1-5 and Comparative Examples 1-4

[0079]

[0080] As can be seen from Table 2, the aluminum electrolytic capacitor prepared in this application has good cycle performance and low internal resistance, and the capacitance retention rate is above 96% after 5000 cycles. In Comparative Examples 1 and 2, a single layer of electrolytic paper is used, and conductive graphite is not adsorbed. The obtained aluminum electrolytic capacitor has high internal resistance and poor cycle performance. In Comparative Examples 3 and 4, only wood pulp fiber is used to prepare the substrate layer, and the microporous layer does not adsorb conductive graphite powder. The cycle performance and internal resistance of the obtained aluminum electrolytic capacitor are worse than those of the aluminum electrolytic capacitor obtained in the embodiment.

[0081] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing an aluminum electrolytic capacitor, characterized in that: At least the following steps are included: Winding the anode foil, the double-layer electrolytic paper and the cathode foil into a core package; Performing an impregnation treatment on the core package; Drying the impregnated core package into a shell to form an aluminum electrolytic capacitor; The double-layer electrolytic paper comprises a microporous layer and a substrate layer, and the microporous layer is arranged close to the anode foil, conductive graphite is adsorbed on the microporous layer, the raw material of the microporous layer is bamboo pulp fiber, and the raw material of the substrate layer is bamboo pulp fiber and wood pulp fiber; The preparation method of the double-layer electrolytic paper comprises the following steps: After bamboo pulp and wood pulp are fully dispersed and mixed, they are transferred to a pulping machine for pulping, and then a papermaking machine is used to prepare a substrate layer; After bamboo pulp is fully deflated, it is transferred to a pulping machine for pulping, and then a microporous layer is prepared using a papermaking machine; Dispersing conductive graphite in a dispersant and spraying or soaking the microporous layer; The substrate layer and the microporous layer adsorbing the conductive graphite are pressed and compounded, and then dried to obtain a double-layer electrolytic paper.

2. The method for preparing an aluminum electrolytic capacitor according to claim 1, characterized in that: The thickness of the microporous layer is 30-50 μm and the density is 0.55-0.70 g / cm 3 .

3. The method for preparing an aluminum electrolytic capacitor according to claim 1, characterized in that: The thickness of the substrate layer is 40-60 μm, and the density is 0.65-0.80 g / cm 3 .

4. The method for preparing an aluminum electrolytic capacitor according to claim 1, characterized in that: The beating degree of the microporous layer is 90-95°SR, and the beating degree of the substrate layer is 85-90°SR.

5. The method for preparing an aluminum electrolytic capacitor according to claim 1, characterized in that: The weight concentration of the conductive graphite is 0.01-0.1 g / ml, and the dispersant is a dispersed aqueous solution of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate).

6. The method for preparing an aluminum electrolytic capacitor according to claim 1, characterized in that: The impregnation treatment comprises at least the following steps: Impregnating the core package with the dispersion liquid to obtain a core package impregnated with the dispersion liquid; impregnating the core package impregnated with the dispersion liquid with a forming liquid to obtain a formed core package; The formed core package is impregnated with electrolyte to obtain a core package impregnated with electrolyte.

7. The method for preparing an aluminum electrolytic capacitor according to claim 6, characterized in that: The electrolyte includes at least one of boric acid, phosphoric acid and adipic acid, the dispersion liquid is a dispersed aqueous solution of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate), and the chemical forming liquid is an aqueous solution of adipic acid amine.

Citation Information

Patent Citations

  • Capacitor and preparation method thereof, electronic equipment, electronic firecracker and arrangement method thereof

    CN112863884A

  • Composite electrolytic paper for capacitor and preparation method thereof

    CN114429864A

  • Novel solid aluminum electrolytic capacitor and preparation method thereof

    CN114974899A